Temperature, oxygen, and vegetation controls on decomposition in a James Bay peatland. Issue 6 (1st June 2015) - Philben, Michael; Holmquist, James; MacDonald, Glen; Duan, Dandan; Kaiser, Karl; Benner, Ronald
Abstract The biochemical composition of a peat core from James Bay Lowland, Canada, was used to assess the extent of peat decomposition and diagenetic alteration. Our goal was to identify environmental controls on peat decomposition, particularly its sensitivity to naturally occurring changes in temperature, oxygen exposure time, and vegetation. All three varied substantially during the last 7000 years, providing a natural experiment for evaluating their effects on decomposition. The bottom 50 cm of the core formed during the Holocene Climatic Optimum (~7000–4000 years B.P.), when mean annual air temperature was likely 1–2°C warmer than present. A reconstruction of the water table level using testate amoebae indicated oxygen exposure time was highest in the subsequent upper portion of the core between 150 and 225 cm depth (from ~2560 to 4210 years B.P.) and the plant community shifted from mostly Sphagnum to vascular plant dominance. Several independent biochemical indices indicated that decomposition was greatest in this interval. Hydrolysable amino acid yields, hydroxyproline yields, and acid:aldehyde ratios of syringyl lignin phenols were higher, while hydrolysable neutral sugar yields and carbon:nitrogen ratios were lower in this zone of both vascular plant vegetation and elevated oxygen exposure time. Thus, peat formed during the Holocene Climatic Optimum did not appear to be more extensively decomposed than peat formed during subsequent cooler periods. Comparison with a core from the West Siberian Lowland, Russia, indicates that oxygen exposure time and vegetation are both important controls on decomposition, while temperature appears to be of secondary importance. The low apparent sensitivity of decomposition to temperature is consistent with recent observations of a positive correlation between peat accumulation rates and mean annual temperature, suggesting that contemporary warming could enhance peatland carbon sequestration, although this could be offset by an increasing contribution of vascular plants to the vegetation.